Effects of the Photosystem II Inhibitors CCCP and DCMU on Hydrogen Production by the Unicellular Halotolerant CyanobacteriumAphanothece halophytica - Sunisa Pansook; Aran Incharoensakdi; Saranya Phunpruch (My University, 2019)
The unicellular halotolerant cyanobacterium Aphanothece halophytica is a potential dark fermentative producer of molecular hydrogen (H 2 ) that produces very little H 2 under illumination. One factor limiting the H 2 photoproduction of this cyanobacterium is an inhibition of bidirectional hydrogenase activity by oxygen (O 2 ) obtained from splitting water molecules via photosystem II activity. The present study aimed to investigate the effects of the photosystem II inhibitors carbonyl cyanide m-chlorophenyl hydrazone (CCCP) and 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) on H 2 production of A . halophytica under light and dark conditions and on photosynthetic and respiratory activities. The results showed that A . halophytica treated with CCCP and DCMU produced H 2 at three to five times the rate of untreated cells, when exposed to light. The highest H 2 photoproduction rates,2.26 ± 0.24and3.63 ± 0.26 μ mol H 2 g −1 dry weight h −1 , were found in cells treated with 0.5 μ M CCCP and 50 μ M DCMU, respectively. Without inhibitor treatment, A . halophytica incubated in the dark showed a significant increase in H 2 production compared with cells that were incubated in the light. Only CCCP treatment increased H 2 production of A . halophytica during dark incubation, because CCCP functions as an uncoupling agent of oxidative phosphorylation. The highest dark fermentative H 2 production rate of39.50 ± 2.13 μ mol H 2 g −1 dry weight h −1 was found in cells treated with 0.5 μ M CCCP after 2 h of dark incubation. Under illumination, CCCP and DCMU inhibited chlorophyll fluorescence, resulting in a low level of O 2 , which promoted bidirectional hydrogenase activity in A . halophytica cells. In addition, only CCCP enhanced the respiration rate, further reducing the O 2 level. In contrast, DCMU reduced the respiration rate in A . halophytica.
Keywords: DCMU; Photosynthetic Processes and Mechanisms